2016
DOI: 10.1177/1420326x16666315
|View full text |Cite
|
Sign up to set email alerts
|

A unified method to compute limits of acceptability for thermal comfort and indoor air quality at the workplace

Abstract: As a part of their very wide range of applications, international standards also represent an excellent technical support to the legislation on comfort and health at the workplace. The existing standards on thermal comfort and on indoor air quality both include limits of acceptability which strongly depend on the category chosen for the investigated work environment. Therefore, the same situation can easily meet compliant or largely exceed specified limits depending on which category is applied. Unfortunately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In fact, many office buildings have significant sources of air pollution, possibly due to inadequate provision of the ventilation system. Research also focuses on computing acceptability limits for IAQ at workplace (Freda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many office buildings have significant sources of air pollution, possibly due to inadequate provision of the ventilation system. Research also focuses on computing acceptability limits for IAQ at workplace (Freda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in managing indoor spaces where the modern population spend at least 80% of their time has increased following research on the negative effects of highly concentrated indoor pollutants on the health and productivity of indoor occupants [ 1 , 2 ]. Therefore, air purification technologies that withdraw indoor air pollutants such as fine dust and radon are in demand [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indoor air pollution is the third leading cause of air pollution worldwide, after bituminous coal and photochemical smog pollution [ 1 ]. High concentrations of indoor pollutants can lead to poor indoor air quality (IAQ), which has negative effects on human health and productivity [ 2 , 3 ]. Many investigations and studies have revealed an indoor CO 2 level higher than 1000 ppm [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%